Preoperative computed tomography assessment of skeletal muscle mass is valuable in predicting outcomes following hepatectomy for perihilar cholangiocarcinoma. Issue 6 (June 2015) - Coelen, Robert J.S.; Wiggers, Jimme K.; Nio, Chung Y.; Besselink, Marc G.; Busch, Olivier R.C.; Gouma, Dirk J.; van Gulik, Thomas M.
Abstract: Background: Liver surgery for perihilar cholangiocarcinoma (PHC) is associated with high rates of morbidity and mortality. Objectives: This study investigated the impact of low skeletal muscle mass on short- and longterm outcomes following hepatectomy for PHC. Methods: Patients included underwent liver surgery for PHC between 1998 and 2013. Total skeletal muscle mass was measured at the level of the third lumbar vertebra using available preoperative computed tomography images. Sex-specific cut-offs for low skeletal muscle mass were determined by optimal stratification. Results: In 100 patients, low skeletal muscle mass was present in 42 (42.0%) subjects. The rate of postoperative complications (Clavien–Dindo Grade III and higher) was greater in patients with low skeletal muscle mass (66.7% versus 48.3%; multivariable adjusted P = 0.070). Incidences of sepsis (28.6% versus 5.2%) and liver failure (35.7% versus 15.5%) were increased in patients with low skeletal muscle mass. In addition, 90-day mortality was associated with low skeletal muscle mass in univariate analysis (28.6% versus 8.6%; P = 0.009). Median overall survival was shorter in patients with low muscle mass (22.8 months versus 47.5 months; P = 0.014). On multivariable analysis, low skeletal muscle mass remained a significant prognostic factor (hazard ratio 2.02; P = 0.020). Conclusions: Low skeletal muscle mass has a negative impact on postoperative mortality and overall survival following resection of PHC and should therefore be considered in preoperative risk assessment.